2020
DOI: 10.1042/bsr20201006
|View full text |Cite
|
Sign up to set email alerts
|

β-glucan from Lentinus edodes inhibits breast cancer progression via the Nur77/HIF-1α axis

Abstract: Background: β-glucan from Lentinus edodes(LNT) is a plant-derived medicinal fungus possessing significant bioactivities on anti-tumor. Both hypoxia-induced factor-1α (HIF)-1α and Nur77 have been shown to be involved in the development of breast cancer. However, there is yet no proof of Nur77/HIF-1α involvement in the process of LNT-mediated tumor-inhibition effect. Methods: Immunohistochemistry, immunofluorescence and hematoxylin-eosin staining were used to investigate tumor growth and metastasis in MMTV-PyMT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
(48 reference statements)
0
14
0
Order By: Relevance
“…Qin et al reported that Nur77 promotes cigarette smoke‐induced autophagic cell death by increasing the dissociation of Bcl2 from beclin‐1 38 . Abnormal expression or function of Nur77 can also lead to various diseases, including breast cancer 27,39,40 . Previous studies have reported that p62 plays a role in inhibiting cell autophagy signals; affects proliferation, differentiation, and apoptotic events; is abnormally expressed as an oncogenic factor in several types of tumors; and inhibits the mTOR signaling pathway to coregulate tumorigenesis 41,42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qin et al reported that Nur77 promotes cigarette smoke‐induced autophagic cell death by increasing the dissociation of Bcl2 from beclin‐1 38 . Abnormal expression or function of Nur77 can also lead to various diseases, including breast cancer 27,39,40 . Previous studies have reported that p62 plays a role in inhibiting cell autophagy signals; affects proliferation, differentiation, and apoptotic events; is abnormally expressed as an oncogenic factor in several types of tumors; and inhibits the mTOR signaling pathway to coregulate tumorigenesis 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…The cells were seeded in 6-well or 24-well plates at a density of 10 5 cells/cm 2 a day before the experiments. Tumor necrosis factor-α (TNF-α) (20 ng/mL) and different concentrations of LNT (50,125,250,500, and 1000 μg/mL) were added to the cells at 70%-80% confluence, and the plates were incubated for 24 h. 27 Conditioned medium was prepared by culturing tumor cells in medium supplemented with β-glucans or phosphate buffer (PBS) for 24 h, and the supernatant was used as the medium for culturing the macrophages; after 24 h of incubation in the conditioned medium, the supernatant of the macrophage culture was used to treat T47D tumor cells.…”
Section: Cell Culture and Cell Treatment Conditionsmentioning
confidence: 99%
“…NR4A1 is a well-studied transcription factor, and recent researches focus on identifying its genomic and non-genomic effects in cancers, including melanoma ( 106 ), breast cancer ( 107 ), and colorectal cancer ( 31 ). As described above, NR4A1 exhibits important functions in cancer cell metabolic reprogramming.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous molecular targets of mushroom-derived β-glucan involve NF-κB inhibitors, protein kinase inhibitors, modulators of G1/S and G2/M checkpoints, inhibitors of MAPK protein kinase signaling pathways, cyclooxygenase inhibitors, and DNA polymerase inhibitors (for review, see Zaidman, Yassin, Mahajna, and Wasser (2005) [ 93 ]). In cases of lentinan, recent observation suggested that the breast cancer progression inhibition is modulated via the Nur77/HIF-1α axis [ 115 ]. The authors speculate that HIFs might be a potential target in breast cancer treatment.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Some direct effects on lung cancer cells were also described for β-glucan from Antrodia cinnamomea, with the supposed mechanism being regulation of the TGFβ/AKT/GSK3β axis [ 126 ]. β-glucan from Lentinus edodes can in some cases inhibit proliferation of breast cancer cells when used simultaneously with hypoxic conditions [ 115 ]. The problem of all these studies, however, is the fact that none of them were ever independently repeated.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%